Oleic Acid and Succinic Acid: A Potent Nutritional Supplement in Improving Hepatic Glycaemic Control in Type 2 Diabetic Sprague-Dawley Rats - Kemmoy G. Lattibeaudiere; Ruby Lisa Alexander-Lindo (Hindawi Limited, 2024)
Nutritional supplements are gaining traction for their effects in mitigating the impacts of various health conditions. In particular, many supplements are being proposed to reduce the impacts of type 2 diabetes (T2D), a metabolic condition that has reached global epidemic proportions. Recently, a supplement of oleic acid (OA) and succinic acid (SA; 1 : 1, w/w) was reported to improve glycaemic control in type 2 diabetic (T2D) Sprague-Dawley (S-D) rats through ameliorating insulin release and sensitivity. Here, we investigate the effects of the supplement (OA and SA) on hepatic and pancreatic function in T2D S-D rats. Eighteen (18) S-D rats were rendered diabetic and were divided into three equal groups: diabetic control, diabetic treatment, and diabetic glibenclamide. Another 12 S-D rats were obtained and served as the normal groups. The animals were treated daily with the vehicle, OA and SA (800 mg/kg body weight (bw); 1 : 1), or glibenclamide (10 mg/kg bw) which served as the positive control. The findings indicated that treatment with the supplement resulted in a 35.69 ± 4.22% reduction (p=0.006) in blood glucose levels (BGL). Analysis of hepatic enzymes depicted that the nutritional supplement reduced the activity of the gluconeogenesis enzyme, glucose-6-phosphatase (G6P) while improved the activity of catabolic enzymes such as glucose-6-phosphate dehydrogenase (G6PD) and pyruvate kinase (PK). Furthermore, the supplement attenuated oxidative stress through restoration of catalase (CAT) and superoxide dismutase (SOD), while reducing malondialdehyde (MDA) levels. Finally, the supplement showed no liver or kidney toxicity and improved the size and number of pancreatic islets of Langerhans, indicating its potential application in treating T2D. The study highlighted that a supplement of the two organic acids may be beneficial in reducing the rate of pathogenesis of type 2 diabetes. Therefore, it may offer therapeutic value as a dietary or nutritional supplement in the approach against diabetes and its complications.